How do paper and electronic records compare for completeness? A three centre study - Wu, Clara Hoi Ka (Eye (Lond), 2018)
OBJECTIVES: Medical records are legal documentation of patients’ care hence must be accurate and complete for both medical and legal purposes. Electronic patient record (EPR) systems aim to improve the accuracy of documentation, provide better organisation and access of data. This study compares the completeness of traditional note records and EPR in glaucoma patients. METHODS: Using criteria from the April 2009 National Institute for Health and Care Excellence (NICE) guidelines completeness of data entry was compared between EPR and paper notes in three units. Moorfields Eye Hospital (City Road) uses the Openeyes EPR. Bedford Hospital (Moorfields Eye Centre) and Western Eye Hospital use the Medisoft EPR. The standard was set at 100% compliance for predetermined parameters. RESULTS: One hundred seventy paper notes and 270 electronic records were analysed. With the exception of central corneal thickness (p = 0.31), all other key parameters were more consistently recorded in the paper records than in the EPR. Intraocular pressure (p = 0.004), anterior chamber configuration and depth assessments using gonioscopy (p < 0.001), fundus examination (p = 0.015), past medical history (p < 0.001), medication including glaucoma medication (p < 0.001) and drug allergies (p < 0.001). CONCLUSIONS: Our results show that paper records are significantly more complete than EPR. This is the case for two different EPRs and three separate sites. We propose additional training to aid data-collection; improving the design of EPRs by investigating factors such as layout and use of forced choice fields.